Language contact and language conflict in Morroco - El Mediouni, Abdeljabbar (Université Mohamed 1er, Faculté des Lettres et des Sciences Humaines, Oujda, 2003)
Recently (De Kadt 1998, Nelde 1990), attention has tuned to the aspects of language contact and language conflict. Social interactions are interpreted differently by different individuals. A large number of studies (Weinstein 1987) support the notion that language contact is language conflict and this latter produces a social conflict. An individual can, under certain conditions, accept the social conventions and the functional distribution of languages in contact. In this case, the context of contact cannot be considered as a source of conflict. Another individual, living in the same social context, refuses to accept the same linguistic distribution. He qualifies it as « repressive » and protests against it. Language contact is probably a theme that gains the interest of many disciplines. Sociology and sociolinguistics are undoubtedly two fields of a paramount importance, which have dealt in the same subject matter (topic). Society has always been the field of concern of both. This is due mainly to the close relationship that binds them. Both have a close accordance with the social life. In an attempt to understand this mentioned relation, i have chosen to work on language contact. This humble study maye nable me to understand how, when and why language contact, under given circumstances, can be classified as either conflict or non-conflict. The main purpose is, in fact, to yield questions in the form of hypotheses that could, in further work, be refind or tested. In the end, i have tried to argue the descriptive frameworks that can enhance my understanding of language contact as a social contact. A summary of the finding and further research are hilighted in the conclusion with the discussion of language contact, in terms of various theories, as a result of social change.
Keywords: Linguistic; Language contact; Language conflict; Morroco